Hak Kepemilikan Tempat Tinggal bagi WNA di Bidang Properti - Suwardi (Perspektif Hukum, 2017)
The residential property sector in Indonesia remains attractive even though there are several factors that have hampered growth over the past two years. The ownership for singles related to property refers to Government Regulation Number 40 of 1996 concerning Building Use Rights, Business Use and Use Rights to Land; Government Regulation Number 41 of 1996 concerning Housing or Residential Houses by Foreigners Domiciled in Indonesia; Law Number 25 of 2007 concerning Investment. Secondly, foreigners can buy or own a house in Indonesia above usufructuary rights, but the maximum time period given is 10 years for land under 2000 square meters. At present, more than 50% of Indonesia's population lives in urban areas. This means that there will be more houses, apartments and condominiums to be built in Indonesian urban areas to meet growing demand. This situation also implies that due to lack of land availability in urban areas, prices tend to rise rapidly, while developers need to increasingly focus on vertical property development such as apartments and condominiums.